Seminars on new EU measures for food security in ACP States - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
In the present economic and political context, significant changes are taking place in food security issues. Nowadays, emphasis is being placed on developing seamless and sensible links between various food security programmes, including emergency...